Sanksi Hukum Kejahatan Peretasan Website Presiden Republik Indonesia - Irzak Yuliardy Nugroho (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: This article discusses about the legal reasoning used by the judges to sanction a criminal law hacking in the website of President of the Republic of Indonesia in State Court of Jember No. 253/Pid.B/2013/PN.JR. The results of the study explained that in Islamic criminal law, there is an element of the crime of access to computer hacking and/or electronic systems belonging to others without permission. This is regulated in article 30 paragraph (1) of act 11 year 2008 on information and electronic transactions which can be analogized as like entering someone else’s home without permission, the act is prohibited by Islam because there are some similarities in its legal argumentation. It is because there is no provision in the text about this criminal act. The criminal act of accessing a computer/electronic systems owned by others without permission in the Islamic Criminal Law (Fiqh Jinayah) can be categorized as jarimah ta'zir submitted to ulil amri, in this case is the government.